The hydraulic performance and clogging characteristics of a subsurface drip irrigation system operating for five years in the North China plain - Li Zaiyu; Mo Yan; Gao Hao; Gong Shihong; Zhang Yanqun; Li Guangyong; Wu Feng (Agricultural Water Management)
Emitter clogging is one of the most significant obstacles to the widespread adoption of subsurface drip irrigation (SDI). This research focused on a five-year-old corn SDI system operating in the North China Plain, where the flow rates and internal clogging material content of 3384 non-pressure compensation emitters (accounting for 51.2 % of the total number of emitters) were measured through excavation. This research explored the response patterns of the emitter relative discharge (Dra), Christiansen uniformity coefficient (Cu), flow index (x), and clogging substance content in various parts of the emitters to different levels of irrigation, nitrogen application, and aeration. The results revealed that Dra and Cu significantly decreased (p < 0.05) with increasing nitrogen application, whereas the changes in irrigation and aeration were not statistically significant. The average Dra and Cu for the entire system were 88.3 % and 91.2 %, respectively, indicating good uniformity of the water distribution in the SDI system. The average x of the emitters increased from 0.47 before installation to 0.53, suggesting a transition from turbulent flow to a partially turbulent flow state, which increased the risk of emitter clogging. Both Dra and Cu decreased linearly with increasing x (R2=0.64–0.78). The proportions of clogging substances in the emitter flow channels (mc), outlet (mo), and intrusion root (mr) dry weight were 28.9 %, 69.3 %, and 1.8 % of the total clogging substance dry weight (M), respectively. The particle size distributions of the clogging substances at the outlets were similar to those of the surrounding soil, which was caused mainly by negative pressure suction. Root intrusions were mostly concentrated at the outlets, with a small portion entering the flow channels, accounting for 4.3–20.1 % of the total flow channel length. Owing to the well-designed pressure regulation and air exhaust system used in this SDI research, along with higher soil moisture in the crop root zone, the negative linear relationship between Dra and mc was most significant (p < 0.01). Based on time projection, this SDI system could operate normally for 8–11 years (Dra, Cu ≥ 80 %). To achieve a life of more than 20 years, additional acid/chlorine treatments, which supplement the existing system components and the current practice of flushing twice annually, are necessary.